Features of ADP-induced platelet aggregation in patients with community-acquired pneumonia 3-d group and its changes during treatment - Syvolap, V. V.; Kurilets, L. O.; Ryazanova, O. D. (Zaporozhye Medical Journal, 2016)
Introduction. Especially dangerous are forecast of hemorrhagic complications of pneumonia. Therefore, the study of aggregation properties of platelets in patients with community acquired pneumonia third group is the most important task of modern pulmonology. Aim of this work was studying of the features of ADP-induced platelet aggregation in patients with community acquired pneumonia third group. Material and methods. In an open prospective study included 50 patients with community acquired pneumonia the third group and 30 healthy individuals. The functional activity of platelets analyzed by the method of Born on platelet aggregation analyzer AR 2110 «SOLAR» (Belarus). As an inducer of aggregation used bacterial 5'-adenosine disodium salt dyphosphorus acid («Sigma Aldrich», USA) in a final concentration of 5 mM/l. Results. In patients with community acquired pneumonia 3-d group compared to the practically healthy individuals revealed a significant degree of inhibition of ADP-induced platelet aggregation by 37% (p<0.05). Also there was likely reduce the time of ADP-induced platelet aggregation at 46.7% (p<0.05). The rate of ADP-induced platelet aggregation in patients with community acquired pneumonia tended to decrease with 54.01±2.68% / min. to 46.00±3.99% / min. and almost reached the limits of statistical probability (p=0.057). Under the influence of treatment there was a further significant decrease only the degree of ADP-induced platelet aggregation by 12.5% (p<0.05). Indicators of time and rate of aggregation were not significantly changed. Conclusions. In patients with community acquired pneumonia 3-d group observed decrease of degree and time of ADP-induced platelet aggregation. There is a further decrease of the degree of ADP-induced aggregation during treatment, without significant alteration of speed and time aggregation.